Efficacy of add-on Ayurveda and Yoga intervention in health care workers of tertiary care hospital during COVID-19: Randomized controlled trial. (August 2022) - Sharma, Vandna; Khuntia, Bharat Krushna; Soneja, Manish; Huddar, Vitthal G.; Ramakrishnan, S.; Sharma, Payal; Rathore, Shubhangi; Valliappan, Varun; Wadhawan, Mohit; Chhabra, Varun; Agarwal, Aman; Jat, Mansingh; et al.
Abstract: Background: The present study aimed to evaluate the safety and prophylactic efficacy of add-on Comprehensive Ayurveda and mindfulness-based Yoga (CAY) regimen to standard care among HealthCare Workers (HCWs) against COVID-19. Materials and methods: This prospective single-blind (outcome assessor-blinded) RCT was conducted in tertiary care hospital in Delhi during July 2020–April 2021. HCWs of both sexes were randomized to add-on CAY intervention or control group. The primary outcomes were the incidence of confirmed COVID-19 positive cases and influenza-like illness events (ILI). Secondary outcomes were anxiety (GAD-7), depression (PHQ-9), and quality of life (SF-36) at the end of 12 weeks. Results: Three hundred fifty-six participants (181 in intervention and 175 in the control group) were randomized. With the modified intention to treat approach, we analyzed 309 participants. The mean age for the intervention and control group was 39.3 ± 10.1 and 36.6 ± 10 years, respectively. Incidence of COVID-19 event was higher in control group compared to CAY group (16 of 164 [9.8%] vs. 11 of 145 [7.6%]; P = 0.50). The incidence of ILI events was also higher in the control group as compared to the CAY group (14 of 164 [8.5%] vs 9 of 145 [6.2%]). The health change domain of the SF-36 questionnaire showed statistically significant improvement in the CAY group as compared to the control group ( P < 0.01). Conclusion: Incidence of COVID-19 and ILI events was lower in the CAY group compared with the contr ol group, though the difference is not statistically significant. Highlights: Healthcare workers (HCWs) are at more risk of getting COVID-19 infection. Ayurveda & yoga may be effective & safe prophylactic therapies for COVID-19. A. paniculata and T. cordifolia possess anti-viral and immuno-modulatory activity. In this RCT, HCWs were provided comprehensive Ayurveda and yoga therapy for 12 weeks. Incidence of COVID -19 was less in intervention group as compared to control.